2020
DOI: 10.1038/s41598-020-78920-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of extracellular vesicles released by Lactiplantibacillus plantarum BGAN8 and their internalization by non-polarized HT29 cell line

Abstract: In recent years the role of extracellular vesicles (EVs) of Gram-positive bacteria in host-microbe cross-talk has become increasingly appreciated, although the knowledge of their biogenesis, release and host-uptake is still limited. The aim of this study was to characterize the EVs released by the dairy isolate Lactiplantibacillus plantarum BGAN8 and to gain an insight into the putative mechanism of EVs uptake by intestinal epithelial cells. The cryo-TEM observation undoubtedly demonstrated the release of EVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Interestingly, though rarely acknowledged, phagocytosis (e.g., of pathogens like Salmonella typhimurium and Staphylococcus aureus ) can also occur in IEC 34 , though there is no evidence for this with non-pathogenic bacteria. Other investigations of the mechanism of internalization of MV from potentially beneficial bacteria have concluded that endocytosis is primarily clathrin-mediated, as internalization was inhibited by dynasore and chlorpromazine but not filipin III or nystatin 23 , 33 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, though rarely acknowledged, phagocytosis (e.g., of pathogens like Salmonella typhimurium and Staphylococcus aureus ) can also occur in IEC 34 , though there is no evidence for this with non-pathogenic bacteria. Other investigations of the mechanism of internalization of MV from potentially beneficial bacteria have concluded that endocytosis is primarily clathrin-mediated, as internalization was inhibited by dynasore and chlorpromazine but not filipin III or nystatin 23 , 33 .…”
Section: Discussionmentioning
confidence: 96%
“…While the current paper was in preparation, two recent reports found similar results in gram-positive non-pathogenic bacteria. Rubio and colleagues found that Bacillus subtilis MV were internalized and apparently transcytosed by Caco-2 cells in vitro 32 , while Bajic and colleagues demonstrated that MV from Lactiplantibacillus plantarum BGAN8 are endocytosed by HT-29 cells in a clathrin-dependent manner 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the probiotic Lactiplantibacillus plantarum BGAN8, time‐course internalization experiments performed in the presence of specific inhibitors of endocytosis pathways evidenced that the main entry route for secreted vesicles in IECs is the clathrin‐mediated pathway, although the uptake kinetics was slower than that reported for BEVs of Gram‐negative probiotics. Whereas internalized E. coli BEVs were apparent at 15–30 min incubation, more than 1 h was required to detect intracellular L. plantarum BEVs (Bajic et al., 2020 ). Authors suggested that the abundant exopolysaccharide material secreted by this probiotic that accompanied isolated BEVs could cause a trapping effect and delay the interaction of BEVs with epithelial cell membrane structures needed for endocytosis.…”
Section: Interaction Of Bevs With Mammalian Host Cellsmentioning
confidence: 99%
“…L. plantarum BGAN8, L. plantarum BGVL2A-18, and L. plantarum BGPKM22 showed the highest ability to bind Cd ions in aqueous solution and did not significantly differ from each other (Figure 1A). L. plantarum BGAN8 has been well characterized as an EPS producer and microvesicle releaser (Bajic et al, 2020a), and it was therefore chosen for further work. Further, isolated EPS-AN8 was tested for binding Cd.…”
Section: Ability Of Exopolysaccharide-producing Lactobacilli To Adsorb CD Ions and Characterization Of Eps-an8mentioning
confidence: 99%